Implementation of e-Government as an Effort to Improve Website-Based Services in Ciherang Village - Andoyo, Andreas (JLASA (Journal of Law and State Administration), 2024)
Information and communication technology has become a very important need in people's lives, especially in terms of the implementation of public services. The government must be able to adapt to technological changes in order to provide more effective and efficient services to the community. Adequate information technology will provide benefits, especially in saving costs, time and effort. One of the efforts that the government can make is to implement E-Government. The method used in this study is a data collection method including observation, interviews and literature studies as well as for system development using the waterfall model. Based on the results of the research, a website was produced that helps the public access accurate and fast information. The Ciherang Village information system website is expected to help improve the accessibility, effectiveness and efficiency of public services in Ciherang Village.